Análise da percepção das comunidades escolares sobre segurança de trânsito no entorno das escolas do município de São Carlos - S.P - Zani, Kelly Keyth Guimarães (2011)
The rates of traffic accidents have shown a serious public health issue. The incompatibility between the built environment of cities, the behavior of drivers, the great movement of pedestrians under unsafe conditions, becomes Brazil one of the highest rates of traffic accidents worldwide. Trampling stands as the leading cause of death from accidents involving children from five to ten years old. Often, children at this age are starting school, that´s the point having a window of vulnerability in which both expectations about the demands of adults extrapolate the skills that these children are able to offer, if viewed on condition of pedestrians who are expected mature enough to cross streets safely. It s a huge justification, putting into practice investments researches focused on the preservation and integrity of life of children and teenagers. The school grounds are daily destination for millions of children worldwide, this study tried to identify the perception of groups of people who use the areas surrounding the school, in relation to traffic safety. The opinions were issued through completing questionnaires, using a Likert´s scale guided exclusively for engineering, traffic education and legal effort. This scale is widely used to verify people's opinion for a particular topic, because it requires respondents indicate a degree of agreement or disagreement with a series of statements related to the object of study. The diagnosis of these perceptions can contribute to a better understanding of the school environment, particularly related to traffic safety, offering subsidies to technicians responsible to develop policies, strategies and action plans, aimed at road safety. For purposes didactic only, this paper is divided into six chapters. The first presents the introduction, purpose and structure of the work, the second brings the theoretical explanation and the three "Es" of traffic insurance, the third section describes the scale used for the interpretation of the questionnaires and procedures for analysis of the questionnaires, the fourth shows the importance of the five (5) groups that guided this research, the fifth chapter is flagged with an overview of the schools and the sample size calculation for the analysis of questionnaires and finally the sixth and final chapter presents the conclusions and findings of the research, as well as some recommendations for further research in the area of traffic safety around the school areas.